Unusual presentation of toxoplasmosis with gastro‐intestinal involvement in HLA non‐identical stem cell transplantation. Issue 4 (24th April 2021) - Hoellinger, Baptiste; Ursenbach, Axel; Villard, Odile; Guffroy, Blandine; Simand, Célestine; Lioure, Bruno
Abstract: Toxoplasmosis is a life‐threatening infection in allogenic stem cell recipients usually involving the brain or retina and more rarely lungs or bone marrow. Digestive involvement has only been reported in AIDS patient. We report about a 38‐year‐old man who received a haploidentical allograft for acute myeloid leukemia and developed an unusual digestive presentation with severe protein‐losing enteropathy following grade III acute digestive GvHD treated with steroids and ruxolitinib. Diagnosis was brought up because of concomitant brain involvement. Digestive symptoms fully recovered after treatment with sulfamethoxazole‐trimethoprim. Digestive toxoplasmosis could be considered as a differential diagnosis or complication of severe digestive GvHD.